(untitled) (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research aims to find out a comparative score between multiple choice and cloze test toward student s reading comprehension achievement at SMK Negeri 1 Tombulu This research used quantitative research with the type of comparative research that used the test method The subject in this research were the first grade students of SMK Negeri 1 Tombulu The data collection technique used two types of tests first is multiple choice objective consist of 20 number and second is cloze test consist of 20 number The writer used the IBM SPSS Statistics Program and the Independent Sample T Test formula to analyse the data The results showed that the average score of students reading on the multiple choice test was 81 40 while the average score on the cloze test was 58 00 This value indicates that the multiple choice obtains higher results than the cloze test It is proved that the significance value of sig 2 tailed is lt;0 001 or has a value of 0 000 That is sig value 2 tailed lt; 0 05 According to the independent sample t test it can be concluded that H0 is rejected and Ha is accepted This means that the multiple choice test is better to assess students reading comprehension achievement in first grade students of SMK Negeri 1 Tombulu < p>